Conflito entre trabalho e família e estratégias de conciliação em pessoas casadas - Techio, Gabriela (2021)
The experience of conflict between the demands of work and family is expected in the routine of individuals who occupy different roles, such as the role of the worker, father/mother, and spouse. However, when the conflict between work and family becomes frequent, losses are observed in the well-being of individuals and their family and professional relationships. Faced with this, people will make use of strategies to reconcile work and family, which range from individual skills, such as knowing how to manage time, to the search for social support, such as spousal support. This research aimed to understand how married people and children seek to deal with the conflict between work and family, using conciliation strategies. For this, two studies were conducted. The first was a systematic review that aimed to identify the strategies used by married workers and children in situations of conflict between work and family, considering articles published between the years 2014 and 2019. The search for the articles was carried out on bases: Web of Science, Scopus, Ebsco, and Scielo. Initially, 109 articles were found, of which 14 met the eligibility criteria. As a result, the thematic classification identified four categories of strategies: individual efforts to reconcile work and family, the spouse's role, other supports, and career changes. The lack of studies carried out in the country highlighted the need for research on the topic in the Brazilian context. The second study was quantitative research that aimed to investigate the relationship between the conflict between work and family, reconciliation strategies, quality of life, and marital satisfaction of workers, married and with children up to 10 years old. 149 individuals participated in the research, who answered an online questionnaire with different psychological scales. Most respondents (74%) were women and 55% were between 31 and 40 years old. Regarding professional aspects, 66% of workers had employment contracts and 56% worked between 30 and 40 hours a week. Regarding family aspects, all relationships were heterosexual, 69% had lived with their spouse for more than seven years and 58% had only one child. The results showed that the experience of conflict between the domains is mainly characterized by the interference of work in the family. The most used conciliation strategies were: mutual emotional support, positive perspective on the situation of double income, and management and planning skills. Damage in the physical and psychological domains of quality of life appeared as predictors of the conflict between the domains. Marital satisfaction, on the other hand, showed a positive relationship with the strategy of mutual emotional support between spouses. It is noteworthy that the research was conducted during the context of the pandemic of COVID 19 and the results help to understand how people sought to reconcile work and family during social distance. Both studies provide important information for career counselors, clinical psychologists, and human resources professionals to help employees and clients deal with professional and family demands.